Effect of IFN-τ on intestinal flora and metabolomics of Escherichia coli-mediated endometritis in mice - Liu, Pan; Zhang, Yaofeng; Chen, Xu; Tang, Lijun; Xu, Wenxiu; Wang, Guigui; Zhang, Duoqi; Liu, Junfeng (Frontiers in Microbiology, 2025)
Endometritis is a common reproductive disease in dairy cows, which can lead to low fertility or infertility and cause significant economic losses to the dairy farming industry. IFN-τ is a type I interferon that may exert significant anti-inflammatory effects in inflammatory diseases. With breakthroughs in microbial mapping sequencing and metabolomics, the role between gut flora and host metabolism and disease has been revealed from a completely new perspective. Therefore, the aim of this study was to investigate the role of IFN-τ in a mouse model of E. coli-induced endometritis by 16S rRNA sequencing and LC-MS untargeted metabolomics, the results showed that IFN-τ could affect the flora structure of the mouse intestine. The E. coli-induced endometritis in mice was found to be associated with five different metabolites and three potential metabolic pathways by LC-MS non-targeted metabolomics, which were the major players in the metabolic pathways, namely Arginine biosynthesis, Pyruvate metabolism, Arginine and proline metabolism. This may be an important metabolic pathway for IFN-τ intervention in endometritis mice. Combining the results of gut flora and metabolomics analyses suggest that changes in metabolic pathways may be influenced by gut flora. We hypothesize that IFN-τ is likely to exert its anti-inflammatory effects by regulating the levels of Oscillospira and Clostridium flora in the gut, which in turn affects the expression of five differential metabolites in uterine tissues.